Criminal code - Johnson, Chapman, 1779-1849 (House document (Virginia. General Assembly. House of Delegates), 1842)
December 28, 1842 letter from Chapman Johnson in response to the inquiry of Henry L. Hopkins, chairman of the Committee for Courts of Justice, as to the reasons for the delay in completing the revision of the criminal code of Virginia, and delineated the progress made.